A novel N-arachidonoyl-l-alanine-catabolizing strain of Serratia marcescens for the bioremediation of Cd and Cr co-contamination - Sun, Xiaoyan; Feng, Huiping; Luo, Jialiang; Lin, Li; Zhang, Haixiang; Duan, Yali; Liu, Fan; Zhang, Kailu; Wang, Baijie; Li, Dong; Hu, Yueming; Zhu, Zhiqiang (Environmental research, 2023)
Cadmium (Cd) and chromium (Cr) are widespread contaminants with a high risk to the environment and humans. Herein we isolated a novel strain of Serratia marcescens, namely strain S27, from soil co-contaminated with Cd and Cr. This strain showed strong resistance to Cd as well as Cr. S27 cells demonstrated Cd adsorption rate of 45.8% and Cr reduction capacity of 84.4% under optimal growth conditions (i.e., 30 °C, 200 rpm, and pH 7.5). Microscopic characterization of S27 cells revealed the importance of the functional groups C–O–C, C–H–O, C–C, C–H, and –OH, and also indicated that Cr reduction occurred on bacterial cell membrane. Cd(II) and Cr(VI) bioaccumulation on S27 cell surface was mainly in the form of Cd(OH)2 and Cr2O3, respectively. Further, metabolomic analyses revealed that N-arachidonoyl-l-alanine was the key metabolite that promoted Cd and Cr complexation by S27; it primarily promotes γ-linolenic acid (GLA) metabolism, producing siderophores and coordinating with organic acids to enhance metal bioavailability. To summarize, our results suggest that S27 is promising for the bioremediation of environments contaminated with Cd and Cr in tropical regions. [Display omitted] •A novel Serratia marcescens strain S27 showing Cd and Cr resistance was isolated.•S27 showed the ability to adsorb Cd and reduce Cr.•Cr was reduced by S27 on its cell surface.•S27 mainly secreted organic acids to enhance Cd and Cr bioavailability.•S27 appears promising for the bioremediation of Cd/Cr-contaminated soil.